Is a Low Dose of Concomitant Chemotherapy With Extended-Field Radiotherapy Acceptable as an Efficient Treatment for Cervical Cancer Patients With Metastases to the Para-Aortic Lymph Nodes?. Issue 8 (1st November 2011) - Kazumoto, Tomoko; Kato, Shingo; Yokota, Harushige; Hasumi, Youko; Kino, Nao; Horie, Kouji; Yoshida, Daisaku; Mizukami, Tatsuji; Saito, Yoshihiro
Abstract : Introduction: Extended-field radiotherapy (EFRT) with the concomitant administration of chemotherapy for patients with advanced cervical cancer has problems regarding its feasibility. The goal of the present study was to assess the tolerability and control rate of low-dose cisplatin with EFRT in patients with imaging-confirmed positive para-aortic lymph nodes (PALs). Methods: Sixteen patients with cervical cancer metastatic to the PALs treated with EFRT were evaluated. The patients included those with stages I to III disease according to the International Federation of Gynecology and Obstetrics with positive PALs diagnosed by computed tomographic imaging. The patients were treated with 25 to 30 mg/m 2 weekly of cisplatin concurrently with radiation therapy. Doses of 48.6 to 51.0 Gy were delivered in 1.8-Gy fractions to the pelvis and included the PALs field. In addition, boost doses for the involved nodes of PALs were delivered contiguously for a total dose of 54 to 60 Gy. All patients were treated with a high dose rate of intracavitary brachytherapy combined with external irradiation. Results: All patients completed the radiation therapy. Grade 3 or 4 acute hematologic toxicity occurred in 7 patients, but there were no cases of grade 3 or 4 nonhematologic acute toxicity. As a late toxicity, 1 patient developed a grade 3 small bowel obstruction. No grade 4 or worse late toxicity occurred. The 4-year overall survival rate was 56.3%. The 4-year distant metastasis-free survival rate was 50%. Seven patients had no recurrence. Eight patients developed distant failures, and another had an isolated local intrapelvic recurrence. Conclusions: A dose greater than 54 Gy for positive PALs in EFRT, in combination with intracavitary irradiation and low-dose weekly cisplatin administration, was safely completed by all of our patients. However, half of the patients had distant failure. This study provided relatively favorable local control and survival. Further considering modifications of the treatment should therefore be encouraged.